Penguatan Literasi Pendidikan Pranikah Bebas Moderasi sebagai Upaya Mitigasi Perceraian Dini - Dari Setiawati; Taufiq Hidayatullah; Zomratus Sa’adah (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
Early marriage and divorce at a young age are among the most prevalent social problems among adolescents. A lack of understanding regarding marital loneliness, coupled with a lack of religious knowledge and life skills, often leads to marriages being faced without proper preparation. This situation necessitates strengthening premarital education literacy, which not only equips the cognitive aspect but also instills values ​​of balance through the concept of moderation. This study focuses on strengthening premarital education literacy without moderation as an effort to mitigate early divorce among adolescents at the Darul Ihsan Islamic Boarding School. The study focuses on how the premarital literacy program, based on the rights and obligations of couples, improved (80%) and family communication skills (78%), based on pre-test and post-test results. Using qualitative descriptive methods through observation, interviews, and documentation, this study found that premarital education literacy without moderation has a positive impact on improving adolescents' readiness for marriage. In addition, this program has also proven relevant in efforts to reduce the risk of early divorce which often arises due to a lack of mental and spiritual readiness among young couples.